A study of antenatal anxiety: comparison across trimesters - Priyambada, Krishna; Pattojoshi, Amrit; Bakhla, Ajay K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of present study was to investigate the antenatal anxiety across all three trimesters of pregnancy. Methods: This is a cross sectional, observational study for which data is collected from consenting subjects attending antenatal Out Patients department for routine antenatal checkup. Data included socio demographic information’s and Hospital Anxiety and Depression Scale and statistical analysis done. Results: Out of 169 Pregnant females 27.8% were during first trimester, 40.8% during second trimester and 31.4% during 3rd trimester. The mean anxiety scores for first, second and third trimester was 10.74±2.97, 11.69±3.09 and 14.20±3.10 respectively. Independent t test revealed significantly higher anxiety scores for third trimester when compared to first trimester scores (t= -6.035, p value = 0.000). Conclusions: This study finds a significantly higher antenatal anxiety during third trimester of pregnancy.